Perbandingan Hasil Klasifikasi Tutupan Lahan dan Penggunaan Lahan Menggunakan Citra Satelit Landsat, Sentinel, dan Pleiades - As, Muhammad Dwi Apriansyah; Ambarwati, Artanty Basilia; Kamila, Tazkia Najwa; Nabila, Salsa Hasna; Alviandi, Rifqi; Putra, Aditya Akasha; Setiawan, Muhammad Ridwan; Somantri, Lili; Himayah, Shafira (Universitas Pendidikan Ganesha, 2025)
Remote sensing has become a significant technology in the analysis and monitoring of land use and vegetation. This technology allows for efficient data collection on a large scale and periodic monitoring of changes in land use and vegetation conditions. This study focuses on comparing the classifications generated from the interpretation of Landsat, Sentinel, and Pleiades satellite images in monitoring the same area. The problem often centers on the accuracy of the interpretation results from the images used, so this study employs three types of images to compare their accuracy using the accuracy test method of the confusion matrix. The land use and land cover in Cihanjuang Rahayu Village, based on the interpretation results from the three types of images, show results that are almost identical and complement each other.